2010
DOI: 10.1071/as09054
|View full text |Cite
|
Sign up to set email alerts
|

Pulsar Timing with the Parkes Radio Telescope for the Fermi Mission

Abstract: Abstract:We report here on two years of timing of 168 pulsars using the Parkes radio telescope. The vast majority of these pulsars have spin-down luminosities in excess of 10 34 erg s −1 and are prime target candidates to be detected in gamma-rays by the Fermi Gamma-Ray Space Telescope. We provide the ephemerides for the ten pulsars being timed at Parkes which have been detected by Fermi in its first year of operation. These ephemerides, in conjunction with the publicly available photon list, can be used to ge… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 78 publications
(73 citation statements)
references
References 52 publications
2
71
0
Order By: Relevance
“…As part of the space-and ground-based pulsar timing campaign supporting Fermi (Smith et al 2008), the pulsar PSR J1357−6429 is being observed at the 64-m Parkes radio telescope (Weltevrede et al 2010b). A total of 74 observations spanning MJDs 54 220 to 55 575 were made in a band centered at 1369 MHz.…”
Section: Radio Timing Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…As part of the space-and ground-based pulsar timing campaign supporting Fermi (Smith et al 2008), the pulsar PSR J1357−6429 is being observed at the 64-m Parkes radio telescope (Weltevrede et al 2010b). A total of 74 observations spanning MJDs 54 220 to 55 575 were made in a band centered at 1369 MHz.…”
Section: Radio Timing Observationsmentioning
confidence: 99%
“…An H-test value of 89.6 is obtained above 100 MeV, corresponding to a pulsed detection significance of ∼8σ (de Jager & Büsching 2010). Figure 1 shows the 25 bin gamma-ray light curve (top panel) as well as the 1.4 GHz radio profile (bottom panel) derived from observations with the Parkes radio telescope (Weltevrede et al 2010b). The gamma-ray peak is offset from the radio pulse by 0.37 ± 0.03 ± 0.01 according to a Lorentzian fit with a full width at half maximum (FWHM) of ∼0.25.…”
Section: Gamma-and X-ray Light Curvesmentioning
confidence: 99%
“…DATA ANALYSIS AND RESULTS 3.1. Radio Ephemeris We used the pulsar ephemeris obtained with the Parkes Observatory, which is a part of the timing program for Fermi (Weltevrede et al 2010). A total of 88 times of pulse arrivals (TOAs) between MJD 54220 and MJD 56512 were used to generate the short time-baseline ephemeris.…”
Section: Observations and Data Reductionmentioning
confidence: 99%
“…Table 1 lists the radio observatories and the validity date ranges for the ephemerides used here. The radio data used in this work came from the Lovell telescope at Jodrell Bank Observatory (JBO, Hobbs et al 2004b); from the Parkes observatory (PKS, Weltevrede et al 2010); and from the Nançay radio telescope (NRT, Cognard et al 2011). The ephemerides completely cover the gamma-ray data sample, except for the millisecond pulsar (MSP) PSR J1732−5049.…”
Section: Gamma-ray Datamentioning
confidence: 99%